Vismia guianensis Improves Survival of Tenebrio molitor and Mice During Lethal Infection with Candida albicans - Arthur André Castro Costa; Elizangela Pestana Motta; Aluísio Silva Oliveira; Pamela Gomes Santos; Josivan Regis Farias; Danielle Cristine Gomes Franco; Mayara Cristina Pinto Silva; Nicolle Teixeira Barbosa; Simone Batista Muniz; Luís Douglas Miranda. Silva; Lucilene Amorim Silva; Claudia Quintino Rocha; et al. (Antibiotics)
Background/Objectives: Vismia guianensis is a vegetal species popularly used to treat fungal infections. This study evaluated the anti-Candida effect of V. guianensis extract after C. albicans lethal infection in Tenebrio molitor larvae and mice. Methods and Results: The chemical profile analysis of a hydroethanolic extract of the leaves of V. guianensis (EHVG) identified 14 compounds. Two sets of experiments used T. molitor larvae. To evaluate toxicity, the uninfected larvae were treated with EHVG or anthraquinone. We considered the following groups: the controls received PBS; ANFO B received amphotericin B (600 mg/mL); EHVG received the extract; and ANTQ received anthraquinone. The extract and anthraquinone resulted in low-level toxicity in the T. molitor larvae. Another set of experiments evaluated the EHVG effect during lethal infection with Candida albicans. The T. molitor larvae were treated intracelomically (ic/10 μL). Treatment with EHVG efficiently improved the survival of the larvae after lethal infection (60%), probably due to the reduction in CFUs. In the mice, the antifungal effect of EHVG was determined in three groups of immunosuppressed Swiss mice (cyclophosphamide, 50 mg/kg/ip) infected with C. albicans (1 × 107 CFU/ip). The control animals were infected and untreated; the ANFO B animals were infected and treated with amphotericin B (600 µg/kg/ip); and the EHVG animals were infected and treated with the extract (5 mg/kg/orally). A SHAM group (uninfected and untreated) was also included. Survival was assessed for 5 days. The extract increased the mice’s survival (60%) and life expectancy, reducing the CFU counts in the peritoneum and blood. EHVG also increased the number of blood neutrophils and peritoneal macrophages. These systemic activities are likely associated with the presence of flavonoids in the extract. Conclusions: The beneficial effects of EHVG in lethal sepsis are related to an antifungal effect, with the number of CFUs decreasing in the larvae and the mice. In addition, EHVG showed immunological activity in the mice, considering immune cell distribution and cytokine production.